RETRACTED: Romanzini et al. Water-Based Supplementation Technology for Grazing Cattle in the Tropics: A Large-Scale Commercial Case Study. Appl. Sci. 2025, 15, 851 - Eliéder Prates Romanzini; Vivienne McCollum; Sarah Mcilveen; Evandro Maia Ferreira; William Luiz de Souza; Marcelo Augusto Oliveira Castro; Priscila Arrigucci Bernardes; Ryan J. Batley; Mark G. Trotter; Diogo Fleury Azevedo Costa (Applied Sciences)
This journal retracts and removes the article titled, “Water-Based Supplementation Technology for Grazing Cattle in the Tropics: A Large-Scale Commercial Case Study” [...]